Analisis Tingkat Pemahaman Perpajakan Pemilik Rumah Kos Pada Wilayah Unit Pelayanan Pemungutan Pajak Daerah (UPPPD) Cempaka Putih Jakarta Pusat - Yuliyawati Yuliyawati; Khairur Razikin (Jurnal Ilmu Administrasi Publik, 2022)
There are many boarding house businesses that have been around for a long time, with the problems like taxpayers who do tax evasion and differences in the data of registered boarding houses with the actual numbers of boarding houses are the backgrounds in this study. For this reason, this study aimed to analyze the Tax Understanding Level of boarding house owners in Cempaka Putih Regional tax collection service unit (UPPPD). Taxpayers are said to understand their tax obligations if they meet 4 indicators, i.e.: understand NPWP (Tax Identification Numbers); Understand rights and obligations: understand tax sanctions, and understand tax rates. The research method used in this study was a qualitative method with descriptive research by conducting  interviews with various informants, i.e. the tax authorities, taxpayers, and academics. Based on the study conducted, it can be seen that there were still many boarding house business owners who did not understand the imposition of taxes on boarding house businesses that are included in the hotel tax on boarding  houses. This happened  because the socialization carried out by the government represented by Cempaka Putih Regional tax collection service unit was still not optimal due to various factors like the lack of Cempaka Putih Regional tax collection service  unit officers and there were still many taxpayers who avoid taxes and the socialization about taxes.